Periodontitis and Alzheimer’s Disease: A Possible Comorbidity between Oral Chronic Inflammatory Condition and Neuroinflammation - Teixeira, Francisco B.; Saito, Miki T.; Matheus, Filipe C.; Prediger, Rui D.; Yamada, Elizabeth S.; Maia, Cristiane S. F.; Lima, Rafael R. (Frontiers in Aging Neuroscience, 2017)
Periodontitis is an oral chronic infection/inflammatory condition, identified as a source of mediators of inflammation into the blood circulation, which may contribute to exacerbate several diseases. There is increasing evidence that inflammation plays a key role in the pathophysiology of Alzheimer’s disease (AD). Although inflammation is present in both diseases, the exact mechanisms and crosslinks between periodontitis and AD are poorly understood. Therefore, this paper aims to review possible comorbidity between periodontitis and AD. Here, the authors discuss the inflammatory aspects of periodontitis, how this oral condition produces a systemic inflammation and, finally, the contribution of this systemic inflammation for worsening neuroinflammation in the progression of AD.